Monotheism between pagans and Christians in late antiquity (Leuven ; Walpole, MA)
vi, 225 sayfa
Keywords: “The fourth century was a major religious battleground. The rise of Christianity, and in particular its dominance from Constantine onwards, marked an important shift in the religious history of the Mediterranean. Christianity saw this change as the victory of its monotheism over the polytheism of paganism. This volume studies how similarities between paganism and Christianity were obscured in the polemic that was waged by Christianity against paganism and in the pagan responses to it. A recurring theme in the papers shows that a concrete religious issue lay at the heart of such polemic: which god can one worship? Christians would restrict worship to their Gid, whereas pagans accepted cultacts for the many traditional deities. The debate about monotheism was therefore not just about conceptions of the divine, but was part of the creation and defence of social, cultural, and religious identities in Late Antiquity. In exploring how the notion of monotheism was shaped by Late Antiquity polemic and how this still influences our understanding of it, this volume also hopes to inform contemporary debates about the dangers of monotheism” --